Radioisotopes Used as Radiotracers for in vitro and in vivo Diagnostics: A Review - Kuntic, Vesna; Brboric, Jasmina; Vujic, Zorica; Uskokovic-Markovic, Snezana (Asian Journal of Chemistry, 2015)
Many of modern diagnostic methods cannot be achieved without radioisotopes. In this review, an overview of the most common radioisotopes (radionuclides) used as markers for in vitro and in vivo studies is provided. To determine the extremely low concentrations of some biological molecules (hormones, drugs, toxins, nucleic acid, etc.) in biological fluids for in vitro studies, b and/or g emitters with different half-lives: H-3, C-14, P-32, P-33, I-125, Cr-51 were frequently used. The majority of all radionuclides (90 %) were utilized for in vivo diagnostics. Single photon emission computed tomography (SPECT) and positron emission tomography (PET) are imaging modalities widely used in diagnostic nuclear medicine. The most important diagnostic radionuclides are technetium-99m (for single photon emission computed tomography) and fluorine-18 (for positron emission tomography).